Legal Politics of Tax Expenditure in Fiscal Incentives in the Mineral and Coal Sector - Hary Kesowo Wibowo; Afdhal Afdhal (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Fiscal incentive policies in Indonesia's mineral and coal sector have been promoted to stimulate investment and economic growth through tax allowances and tax holidays that reduce corporate tax liabilities. This study examines these incentives from a legal and political perspective by positioning them as tax expenditures, representing a sacrifice of state revenue equivalent to public spending. Using normative legal research with conceptual, statutory, and constitutional approaches, the study analyzes taxation, mining, and state finance regulations in light of constitutional principles. The findings indicate that fiscal incentive policies tend to prioritize investment interests over fiscal justice, state revenue optimization, and the constitutional mandate of state control over natural resources. Tax allowances and tax holidays have not been adequately integrated into a framework of fiscal accountability and public oversight, creating tension with the constitutional principles of justice, public benefit, and sustainability. Accordingly, this study proposes reconstructing the legal policy on fiscal incentives by recognizing tax expenditures as state expenditures, strengthening evaluation and oversight mechanisms, and imposing constitutional limits on fiscal incentives to ensure alignment with public prosperity and the sustainable management of natural resources.